THE POSSIBILITIES OF MODERN METHODS OF ABLATION IN NON-RESECTABLE LOCALLY ADVANCED PANCREATIC CANCER - L. I. Moskvicheva; L. O. Petrov; D. V. Sidorov (Исследования и практика в медицине)
TToday, pancreatic cancer is one of the most acute medical and social problems that is connected with features of clinical course of the disease, late manifestation, complexity of diagnostics and rather low efficiency of treatment. More often, this pathology is revealed at late stages, when the radical surgical benefit is not advisable. Until recently, treatment options for patients with metastatic and unresectable locally advanced pancreatic cancer were very limited, the prognosis remained very unfavorable. At the end of the twentieth century, in many countries of the world began to develop new methods of local destruction of unresectable tumors intraabdominal localization, contributing to the relief of symptoms of the tumor process, increase the quality of life and its duration. These include radiofrequency and microwave ablation, high-intensity focused ultrasound therapy, cryoablation, irreversible electroporation and photodynamic therapy. Today, these methods of treatment are actively introduced into practical health care, allow to increase the life expectancy of patients with unresectable tumor processes, along with maintaining or improving its quality. This article presents a literature review of different methods of local treatment in patients unresectable locally advanced pancreatic cancer.